Reduction in systemic glucocorticoid utilization among COPD patients with type 2 inflammation treated with biologics - Truong-An A. Ho; Stephen Dachert; Anugya Mittal; Gerard J. Criner (BMC Pulmonary Medicine)
Abstract Background Systemic glucocorticoids are associated with significant side effects, however, are essential in the treatment of acute exacerbations of chronic obstructive pulmonary disease (COPD). Biologic therapies in COPD with type 2 (T2) inflammation have shown benefit in reducing exacerbations, but their impact on glucocorticoid utilization remains unclear. We aim to examine if use of biologics in COPD patients reduces glucocorticoid burden. Methods A retrospective review of the electronic medical record (2016–2023) was performed. Patients with COPD that were treated with biologics were included. Data collected included demographics, baseline comorbidities, eosinophil count, pulmonary function testing and dispense reports for glucocorticoids. The primary outcomes were a change in the number of glucocorticoid dispenses and total cumulative systemic glucocorticoid dosage, in the year prior and post initiation of therapy. Results 56 patients (mean age 71 ± 8.5) were included in the study. 55% had coronary artery disease, 25% had heart failure, 71% had hypertension, 14% had stroke and 30% had diabetes. Biologics significantly reduced annual glucocorticoid dispenses (3.38 ± 2.58 vs. 2.22 ± 2.33, mean reduction 1.16, 95% CI 0.45–1.87, p = 0.002) and cumulative dosage (1073 ± 831 mg vs. 659 ± 723 mg, mean reduction 413.2 mg, 95% CI 180.8–645.6, p = 0.001). There was no strong association between baseline eosinophil count and glucocorticoid utilization. Conclusions In this real-world cohort of COPD patients with T2 inflammation, the addition of biologic therapies was associated with a significant reduction in systemic glucocorticoid usage, both in terms of dispense frequency and overall total dosage of systemic glucocorticoids. This highlights the potential of biologics to reduce glucocorticoid-related adverse effects in COPD patients.